STUDY OF SUCCESS RATE AND COMPLICATIONS OF PERCUTANEOUS CORONARY INTERVENTION IN CTO INTERVENTION - KHAN, AS; ULLAH, F; KHAN, TI; MURSALIN, MQU; AKBER, S; HAYAT, Y (Biological and Clinical Sciences Research Journal, 2024)
Chronic total occlusion (CTO) is one of the most complex and challenging forms of coronary artery disease, characterized by the complete obstruction of a coronary artery for more than three months. Objective: The primary aim of this study is to assess the success rate of PCI in patients with CTO and to evaluate the frequency and types of complications associated with the procedure. Methods: Patients included in the study were diagnosed with CTO using coronary angiography. The PCI procedures were carried out using standard techniques, and the primary endpoints were technical success and clinical success. Technical success was achieved by less than 30% residual stenosis with a TIMI grade 3 flow in the target vessel. In contrast, clinical success was defined as procedural success without the occurrence of major adverse cardiovascular events (MACE) such as death, myocardial infarction, or stroke within 30 days post-procedure and target vessel revascularization. Results: Among the 200 patients who underwent PCI for CTO, technical success was achieved in 165 patients, reflecting an overall success rate of 82.5%. Clinical success, defined as the absence of MACE, was achieved in 150 patients (75%). The major complications observed included coronary perforation in 10 patients (5%) and contrast-induced nephropathy in 8 patients (4%). Stent thrombosis occurred in 5 patients (2.5%), while 4 patients (2%) succumbed to procedural complications, leading to mortality within 30 days. Other minor complications such as arrhythmias and vascular access-related complications were seen in 20 patients (10%). Despite these complications, the success rates are consistent with current literature on CTO interventions, highlighting the effectiveness of PCI in these challenging cases. Conclusion: The study concluded that PCI for CTO can be performed with a high technical and clinical success rate with an acceptable complication profile. While major complications such as coronary perforation and contrast-induced nephropathy remain a concern, the overall outcomes suggest that PCI is an effective treatment option for CTO patients.